The Differential Impact of Intrafirm Collaboration and Technological Network Centrality on Employees’ Likelihood of Leaving the Firm - Tzabbar, Daniel; Cirillo, Bruno; Breschi, Stefano (Organization Science, 2022)
How does an employee’s centrality in intrafirm research and development activities affect the employee’s propensity for outward mobility? Does this proclivity vary by the type of employment the employee seeks: moving to other firms versus founding a new venture? We maintain that, to answer these questions, we must distinguish between an employee’s centrality in the intrafirm collaboration network and the employee’s centrality in the intrafirm technological recombination network. We utilize the curricula vitae and patent data of corporate inventors at a leading semiconductor company between 1993 and 2012 to test our hypotheses. Contrary to prevailing views, our competing risk model indicates that corporate inventors who are central in the intrafirm collaboration and technological network and, thus, have the most opportunities are less likely to leave the current employer. However, when considering external employment opportunities, their preferences vary. Collaboration-central individuals are more likely to start a new venture than to move to another employer. Their skill in developing interpersonal relationships enables them to attract the tangible and intangible resources needed in a new firm. In contrast, inventors whose technological expertise is central to the firm’s technology recombination network are more likely to move to another employer than to start a new venture. In an established firm, they can leverage their technological know-how using the resources that a new venture would lack. Our theory highlights the trade-offs in employees’ attempts to take advantage of their internal and external value based on their position within the firm’s collaboration and technological networks. Funding: The authors thank LeBow College of Business, SKEMA Business School, and Bocconi University for their financial support. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1535 .